Ferrous ascorbate as well as preparation method and application thereof

By mixing sodium ascorbate with ferrous sulfate hydrated after metathesis reaction with ethanol, high purity ferrous ascorbate was successfully prepared, solving the problems of low purity of the product and high temperature in the prior art, and improving the preparation efficiency and product stability.

CN119306687APending Publication Date: 2025-01-14ZHONGKAI UNIV OF AGRI & ENG +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411237765.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-04
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

It is difficult to efficiently prepare high-purity ferrous ascorbate ferrous ascorbate in the prior art, and the raw materials used are unstable, the reaction conditions are high and the side reactions are severe, resulting in low purity of the product.

Method used

Sodium ascorbate and ferrous sulfate hydrated at a certain temperature and stirring conditions were used to perform metathesis reaction, and then mixed with ethanol to obtain high-purity ferrous ascorbate through freeze-drying, which avoids the instability and high-temperature reaction of ferrous carbonate in traditional methods. .

Benefits of technology

The high-purity preparation of ferrous ascorbate is achieved, the difficulty of reaction is reduced, the use of raw materials is optimized, the generation of side reactions is avoided, and the stability and application value of the product are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119306687A_ABST
    Figure CN119306687A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of ascorbic acid derivatives, and particularly relates to ferrous ascorbate as well as a preparation method and application thereof. The invention provides a preparation method of ferrous ascorbate, which comprises the following steps: mixing sodium ascorbate, ferrous sulfate and water, and carrying out double decomposition reaction to obtain reaction liquid; and mixing the reaction liquid with ethanol, and separating out the ferrous ascorbate. According to the preparation method provided by the invention, the yield of ferrous ascorbate is relatively high, the preparation method can be realized without too high temperature, and the reaction difficulty is remarkably reduced; meanwhile, the used synthesis raw materials are optimized, the defects that the raw material ferrous carbonate used in an existing method is unstable and difficult to store are overcome, ferrous sulfate is more convenient and practical, and the raw material obtaining difficulty is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ascorbic acid derivatives, and particularly relates to ferrous ascorbate and a preparation method and application thereof. Background Art

[0002] Ferrous ascorbate is a black-purple powder with an odor similar to ink and is easily hygroscopic. Ferrous ascorbate has multiple functional properties of ascorbic acid and iron supplements, and can be used as a safe, non-toxic, and highly effective new food additive and disinfectant. As a new iron source, it has good biocompatibility and can improve the body's absorption and utilization of iron. It can be used to prepare oral rehydration salts or iron chelators to prevent iron deficiency anemia. Due to the presence of ascorbic acid in ferrous ascorbate, it is difficult for iron to be oxidized to Fe 3+ After taking it, the iron in the body will not easily turn into Fe 3+ , excellent stability, and ferrous ascorbate is easily soluble in water. Its absorption rate is higher than that of inorganic iron salts, which can rapidly increase the serum iron value and has little irritation to the gastric mucosa. It is a stable and effective iron supplement for the treatment of exogenous iron deficiency anemia. Its nutritional value is much higher than the sum of the two. Therefore, in the fields of food production and processing, ferrous ascorbate can be used as an antioxidant and nutritional enhancer for processed food; and in the field of medical and health care, ferrous ascorbate is often used to diagnose ascorbic acid deficiency syndrome, iron deficiency syndrome, etc.

[0003] Herbourg P. Rao et al. synthesized ferrous ascorbate by reacting ascorbic acid with FeCl2 in methanol solution in 1999. After testing with the equipment, it was found that there was a large amount of Fe 3+ It can be seen that the purity of ferrous ascorbate produced by this method is low, and the use of methanol as a reaction medium is costly and toxic. Nine years later, Xu Jianzhong et al. synthesized ferrous ascorbate by using FeCO3 made from FeCl2 and ascorbic acid in distilled water with nitrogen at 100°C, with a yield of 68.1%. However, the purity of the product depends on the homemade FeCO3, and the reaction has serious side reactions, and it is also very easy to generate Fe 3 + , resulting in low product purity. Chinese patent CN106699816A provides a ferrous ascorbate with hydrogen sulfate and a preparation method and application thereof, wherein ferrous sulfate and ascorbic acid are used as raw materials in an aqueous system and reacted in a molar ratio of 1:1. The obtained product is a slightly green crystalline powder containing hydrogen sulfate. It can be seen that this scheme is difficult to achieve the preparation of high-purity ferrous ascorbate. Summary of the invention

[0004] The purpose of the present invention is to provide ferrous ascorbate and a preparation method and application thereof. The ferrous ascorbate obtained by the preparation method provided by the present invention has high purity.

[0005] In order to achieve the above object, the present invention provides the following technical solutions:

[0006] The present invention provides a method for preparing ferrous ascorbate, comprising the following steps:

[0007] Mixing sodium ascorbate, ferrous sulfate and water to perform double decomposition reaction to obtain a reaction solution;

[0008] The reaction solution is mixed with ethanol to precipitate the ferrous ascorbate.

[0009] Preferably, the ferrous sulfate is hydrated ferrous sulfate;

[0010] The molar ratio of the sodium ascorbate to ferrous sulfate is 2-3:1.

[0011] Preferably, the volume ratio of the amount of sodium ascorbate to water is 1 mol: 1-50 mL.

[0012] Preferably, the temperature of the metathesis reaction is 30-70° C., and the time is 30-180 min.

[0013] Preferably, the metathesis reaction is carried out under stirring conditions; the stirring speed is 200-400 rpm.

[0014] Preferably, the ethanol is anhydrous ethanol; the mass ratio of water to ethanol is 5-15:10-30.

[0015] Preferably, after mixing the reaction solution and ethanol, the precipitated solid is freeze-dried; the freeze-drying temperature is -80 to -20°C and the time is 18 to 72 hours.

[0016] The present invention also provides ferrous ascorbate obtained by the preparation method described in the above technical solution, wherein the iron content of the ferrous ascorbate is 8% to 13%.

[0017] The invention also provides the use of ferrous ascorbate in preparing antibacterial preparations.

[0018] The invention also provides the application of ferrous ascorbate in DNA detection.

[0019] The present invention provides a method for preparing ferrous ascorbate, comprising the following steps: mixing sodium ascorbate, ferrous sulfate and water, performing double decomposition reaction, and obtaining a reaction solution; mixing the reaction solution with ethanol, and precipitating the ferrous ascorbate. The ferrous ascorbate obtained by the preparation method provided by the present invention has high purity; at the same time, the synthetic raw materials used are optimized, the shortcomings of the raw material ferrous carbonate used in the existing method that is unstable and difficult to preserve are avoided, and the use of ferrous sulfate is more convenient and practical, which reduces the difficulty of obtaining raw materials.

[0020] Furthermore, the preparation method provided by the present invention can be realized without using excessively high temperatures, thus significantly reducing the difficulty of the reaction. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0022] Figure 1 A flow chart of the preparation method provided by the present invention;

[0023] Figure 2 The test solution prepared by the ferrous ascorbate obtained in Example 1 and Fe 3+ Physical picture of visual colorimetry of standard solution;

[0024] Figure 3 The infrared spectra of ferrous ascorbate and sodium ascorbate obtained in Example 1 are shown in the figure;

[0025] Figure 4 TG-DTG curve of ferrous ascorbate obtained in Example 1;

[0026] Figure 5 is the TG-DTG curve of sodium ascorbate;

[0027] Figure 6 The UV spectra of ferrous ascorbate, ascorbic acid and sodium ascorbate obtained in Example 1;

[0028] Figure 7 The standard curve for the test of ferrous ascorbate complexed ferrous iron content obtained in Example 1;

[0029] Figure 8 The DPPH free radical scavenging rate data of ferrous ascorbate, sodium ascorbate, ascorbic acid, nicotinic acid and sodium citrate obtained in Example 1 are shown in FIG.

[0030] Fig. 9ABTS of ferrous ascorbate, sodium ascorbate, ascorbic acid, nicotinic acid and sodium citrate obtained in Example 1 + Free radical scavenging rate data graph;

[0031] Fig.10 This is a stability test diagram of the ferrous ascorbate obtained in Example 1 at a pH of 2;

[0032] Fig.11 This is a stability test diagram of the ferrous ascorbate obtained in Example 1 at a pH of 4;

[0033] Fig.12 This is a stability test diagram of the ferrous ascorbate obtained in Example 1 at a pH of 6;

[0034] Fig.13 This is a stability test diagram of the ferrous ascorbate obtained in Example 1 at a pH of 7;

[0035] Fig.14 This is a stability test diagram of ferrous ascorbate obtained in Example 1 at pH 8;

[0036] Fig.15 This is a graph showing the antibacterial ability of ferrous ascorbate obtained in Example 1 against Staphylococcus aureus measured by agar diffusion method;

[0037] Fig.16 This is a graph showing the antibacterial ability of ferrous ascorbate obtained in Example 1 against Escherichia coli measured by agar diffusion method;

[0038] Fig.17 is the OD of the Staphylococcus aureus culture cultured with ascorbic acid and ferrous ascorbate obtained in Example 1 630 Growth curve chart;

[0039] Fig.18 is the OD of the Escherichia coli culture cultured with ascorbic acid and ferrous ascorbate obtained in Example 1 630 Growth curve chart;

[0040] Fig.19 is the OD of Staphylococcus aureus after being treated with ferrous ascorbate obtained in Example 1 at different concentrations 630 Growth curve chart;

[0041] Fig. 20 is the OD of Escherichia coli after being treated with ferrous ascorbate obtained in Example 1 at different concentrations 630 Growth curve chart;

[0042] Fig.21 This is a graph showing the test results of the interaction between ferrous ascorbate obtained in Example 1 and DNA of different concentrations. DETAILED DESCRIPTION

[0043] The present invention provides a method for preparing ferrous ascorbate, comprising the following steps:

[0044] Mixing sodium ascorbate, ferrous sulfate and water to perform double decomposition reaction to obtain a reaction solution;

[0045] The reaction solution is mixed with ethanol to precipitate the ferrous ascorbate.

[0046] In the present invention, unless otherwise specified, all raw material components are commercially available products well known to those skilled in the art.

[0047] The invention mixes sodium ascorbate, ferrous sulfate and water, and performs double decomposition reaction to obtain a reaction solution.

[0048] In the present invention, the ferrous sulfate is preferably hydrated ferrous sulfate, more preferably ferrous sulfate heptahydrate; the molar ratio of sodium ascorbate to ferrous sulfate is preferably 2 to 3:1, more preferably 2 to 2.8:1, and most preferably 2 to 2.5:1. The present invention uses sodium ascorbate to replace the traditional direct use of ascorbic acid, reducing the production of trivalent iron and hydrogen sulfate ions in the side reactions, and does not require the participation of toxic reagent methanol, thereby obtaining higher purity ferrous ascorbate, and only requires a relatively low temperature for stable reaction. The hydrated ferrous sulfate powder used in the present invention is more stable and inexpensive than ferrous sulfate, and produces the same chemical properties after being dissolved in water.

[0049] In the present invention, the volume ratio of the amount of sodium ascorbate to water is preferably 1 mol: 1 to 50 mL, more preferably 1 mol: 1 to 25 mL.

[0050] In the present invention, the temperature of the double decomposition reaction is preferably 30-70°C, more preferably 30-55°C, most preferably 30-50°C; the time is preferably 30-180 min, more preferably 40-120 min.

[0051] In the present invention, the metathesis reaction is preferably carried out under stirring conditions; the stirring speed is preferably 200 to 400 rpm, more preferably 200 to 300 rpm.

[0052] In the present invention, the waste liquid generated by the preparation method is preferably used as a disinfectant, more preferably an environmentally friendly disinfectant. 2+ The mixture is a Fenton reagent-like substance, which has excellent bactericidal effect and is very friendly to humans and the environment.

[0053] In the present invention, the ethanol is preferably anhydrous ethanol; the mass ratio of water to ethanol is preferably 5-15:10-30, more preferably 5-10:15-25.

[0054] In the present invention, after mixing the reaction solution and ethanol, it is preferred that the process further includes sequentially performing sealing, standing, filtering, washing and freeze-drying; the standing temperature is preferably -18 to 4°C, more preferably -18 to -5°C; the time is preferably 36 to 72 hours, more preferably 36 to 60 hours; the washing reagent is preferably ethanol, more preferably anhydrous ethanol; the freeze-drying temperature is preferably -80 to -20°C, more preferably -80 to -40°C; the time is preferably 18 to 72 hours, more preferably 30 to 60 hours; the present invention does not have any special limitation on the sealing and filtering processes, and the processes well known to those skilled in the art may be used.

[0055] The preparation method provided by the present invention has a yield of 50-54% of ferrous ascorbate, a high product purity, and can be achieved without excessively high temperatures, significantly reducing the difficulty of the reaction; at the same time, the synthetic raw materials used are optimized, avoiding the shortcomings of the raw material ferrous carbonate used in the existing method being unstable and difficult to preserve, and using ferrous sulfate is more convenient and practical, reducing the difficulty of obtaining the raw materials. Further, the present invention is compared with the existing synthesis scheme of ferrous ascorbate, and the optimal reaction temperature is significantly reduced from 100°; the way to obtain the reactant is changed from vacuum drying to freeze drying; it can be seen that the preparation method provided by the invention is greatly different and advanced from the existing synthesis method.

[0056] The present invention also provides ferrous ascorbate obtained by the preparation method described in the above technical solution, wherein the iron content of the ferrous ascorbate is 8% to 13%, preferably 8% to 10%. The ferrous ascorbate provided by the present invention has a high proportion of ferrous iron to the iron content, and the purity of the ferrous ascorbate in the product after the reaction is high.

[0057] The present invention also provides the use of the ferrous ascorbate described in the above technical solution in the preparation of an antibacterial preparation.

[0058] In the present invention, the antibacterial preparation is preferably an anti-Escherichia coli preparation or an anti-Staphylococcus aureus preparation; the present invention does not have any special limitation on the application process of the ferrous ascorbate in the preparation of the antibacterial preparation, and the process well known to those skilled in the art can be used.

[0059] The present invention also provides the use of the ferrous ascorbate described in the above technical solution in DNA detection.

[0060] The present invention does not have any special limitation on the application process of the ferrous ascorbate in DNA detection, and the process well known to those skilled in the art can be used.

[0061] In order to further illustrate the present invention, the ferrous ascorbate and its preparation method and application provided by the present invention are described in detail below in conjunction with the accompanying drawings and examples, but they should not be construed as limiting the scope of protection of the present invention.

[0062] The preparation method flow chart provided by the present invention is as follows Figure 1 As shown, the specific steps are as described in the embodiments.

[0063] Example 1

[0064] Sodium ascorbate is used to react with ferrous sulfate heptahydrate, and the molar ratio is 2: 1 group, 1.8: 1 group, 1.9: 1 group, 2.1: 1 group, 2.2: 1 group, sodium ascorbate and ferrous sulfate heptahydrate are weighed, put into a beaker, 5mL deionized water is added, put into a magnetic ion stirrer for reaction, and the reaction temperature is 50 DEG C, and the stirring speed is 255rpm. After 60min, 15mL of anhydrous ethanol is added, then sealed with plastic wrap and rubber band, and then a layer of tin foil is put into a refrigerator fresh-keeping layer, and the temperature is constant at 4 DEG C, and it is left to stand for 24h, then taken out, filtered, repeatedly cleaned with ethanol, dried, and frozen for 24h using a freeze dryer, and the black purple powder obtained is ferrous ascorbate. The synthesis data of the present embodiment are as shown in Table 1.

[0065] Table 1 Synthesis data of ferrous ascorbate under different molar ratios described in Example 1

[0066]

[0067]

[0068] As can be seen from Table 1, when the reaction ratio is greater than or equal to 2:1, there is no Fe in the product. 3+ ions. With the increase of sodium ascorbate dosage, the product increases to a certain extent. When the reaction ratio is less than 2:1, there is Fe in the product. 3+ ions. When sodium ascorbate is insufficient, there is not enough ascorbate and Fe 2+ Complexation makes Fe 2+ Oxidized to Fe 3+ .

[0069] Example 2

[0070] Ferrous ascorbate was prepared according to the method of Example 1, wherein the molar ratio of sodium ascorbate to ferrous sulfate heptahydrate was 2:1, except that the reaction temperatures were 30°C, 40°C, 50°C, 60°C, and 70°C, respectively. After the reaction, the presence or absence of Fe 3+ .

[0071] The test results show that the output increases with the increase of temperature and begins to decrease when the reaction temperature is higher than 50°C. When the reaction temperature is higher than 50°C, the product contains Fe 3+ It may be because the temperature increases Fe 2+ The 3d orbital is more likely to lose an electron to become Fe 3+ When the reaction temperature is greater than 50°C, the product contains Fe 3+ ion.

[0072] Example 3

[0073] Ferrous ascorbate was prepared according to the method of Example 1, wherein the molar ratio of sodium ascorbate to ferrous sulfate heptahydrate was 2:1, except that the amount of deionized water was 5 mL group, 10 mL group, 15 mL group, 20 mL group, and 25 mL, respectively, and the weight of the product after the reaction was measured.

[0074] The test results show that when the amount of deionized water is less than or equal to 10mL, the product yield increases with the decrease in the amount of deionized water; ferrous ascorbate is a polyhydroxy compound, which is easily soluble in water according to the principle of like dissolves like, and increasing the amount of water is not conducive to precipitation. From the perspective of cost saving, choosing 5mL of deionized water is the most cost-effective.

[0075] Example 4

[0076] Ferrous ascorbate was prepared according to the method of Example 1, wherein the molar ratio of sodium ascorbate to ferrous sulfate heptahydrate was 2:1, except that the amounts of anhydrous ethanol were 15 mL group, 20 mL group, 25 mL group, 30 mL group, and 35 mL, respectively, and the weight of the product after the reaction was measured.

[0077] The test results show that when the ethanol dosage is greater than or equal to 15 mL, the product yield remains basically unchanged and no Fe 3+ Ions; Ferrous ascorbate is a polar compound, and the polarity of anhydrous ethanol is very low. When the amount of ethanol reaches a certain level, the solubility of ferrous ascorbate remains unchanged. From the perspective of cost saving, choosing 15mL of ethanol is the most cost-effective.

[0078] Example 5

[0079] Ferrous ascorbate was prepared according to the method of Example 1, wherein the molar ratio of sodium ascorbate to ferrous sulfate heptahydrate was 2:1, except that the standing temperature was -18°C and 4°C, and the weight of the product after the reaction was measured.

[0080] The test results show that when the standing time is 24h, the product yield is lower when the freezing temperature is 4℃ than when the freezing temperature is -18℃. The freezing point of water is much different from that of ethanol. The reaction product solution freezes at -18℃, while ethanol is still liquid. From the perspective of energy saving and time cost, it is more economical to choose a freezing temperature of -18℃ for freezing.

[0081] Test Example 1

[0082] Identification of ferric iron in the embodiment of the present invention: Check whether there is Fe in the ferrous ascorbate obtained in Example 1 3+ Use visual colorimetry to perform qualitative analysis and configure Fe 3+ The standard solution is compared with the solution to be tested. Take 1.0g of the sample and place it in a 25mL stoppered cuvette. Add 1mL HCl, add oxygen-free water to the mark, add 25% KSCN solution and shake thoroughly to obtain the solution to be tested. 3+ The standard solution is visually compared with the standard solution. Figure 2 .

[0083] Depend on Figure 2 It can be seen that the solution to be tested is shaken thoroughly to obtain a yellow-green clear solution. 3+ The product solution and the standard Fe 2+ The color of the solution is consistent. This test example can illustrate that there is no trivalent iron ion in the ferrous ascorbate obtained in the experiment, and the product purity is extremely high.

[0084] Test Example 2

[0085] Infrared spectrum test: After mixing the sample obtained in Example 1 (molar ratio of 2:1) and the dried potassium bromide powder, polish and grind until there are no particles, then take an appropriate amount of powder and put it into a model, and then press it into a sheet using a tablet press. Using blank potassium bromide as the background, use a Fourier transform infrared spectrometer to characterize the structure of the sample. Used to identify the synthesis of ferrous ascorbate. Comparison of infrared spectra of ferrous ascorbate (a) and sodium ascorbate (b) Figure 3 shown.

[0086] Depend on Figure 3 It can be seen that ferrous ascorbate is at 3446cm -1 The vicinity is attributed to the stretching vibration of -OH; in sodium ascorbate at 3436cm -1 The stretching vibration of -OH is attributed to the nearby stretching vibration. The shift of the stretching vibration peak of -OH to low frequency is related to the association caused by the interaction force within the molecule. It can be inferred that Fe 2+It forms a coordination bond with the ascorbate ion. The carbonyl group of ascorbic acid does not coordinate with the metal, and the vibrational stretching of the hydroxyl group appears at 1636cm -1 After the coordination, this peak splits into two peaks, 1610 cm -1 and 1628cm -1 Because the vibration of uncoordinated hydroxyl is stronger than that of coordinated hydroxyl, 1628cm -1 It is the vibration of uncoordinated hydroxyl group, 1610cm -1 It is the vibration of the coordinated hydroxyl group. The vibration range of Fe-O is 700~370cm -1 . At 652cm -1 、598cm -1 There are two peaks that are obviously different from sodium ascorbate. Therefore, it can be inferred that Fe 2+ It forms a coordination bond with the ascorbate ion.

[0087] Test Example 3

[0088] Thermogravimetric analysis: Place a dry and clean alumina crucible in a thermogravimetric analyzer and peel it. Then take out the crucible and evenly add 3-5 mg of the sample obtained in Example 1 (molar ratio of 2:1) into it. Then put the crucible back into the thermogravimetric analyzer and set various parameters on the computer program. The atmosphere is nitrogen, the introduction rate is 50 mL / Min, and the measurement is started at a heating rate of 10°C / min. The data of the thermogravimetric (TG) graph is obtained, the first-order derivative of the data is taken to obtain the DTG data, and the data is fitted to obtain the TG-DTG graph. It is used to determine the thermal stability of ferrous ascorbate. The TG-DTG curves of ferrous ascorbate and sodium ascorbate are shown in the figure. Figures 4-5 shown.

[0089] Depend on Figure 4 It can be seen that the heating process of ferrous ascorbate can be divided into three stages. Drying stage (50℃~145℃), volatilization and combustion stage (145℃~198.3℃), residual volatilization and coke combustion stage (198.3℃~700℃). In the drying stage, it is mainly the crystal water and residual ethanol and water in ferrous ascorbate. The weight loss rate reaches the maximum at 123.1℃, and the total mass loss is 6.69%. In the volatilization and combustion stage, ferrous ascorbate begins to decompose. The temperature at this time is just at the decomposition temperature of ascorbic acid, so the mass drops sharply. The weight loss rate reaches the maximum at 198.3℃, and the total mass loss is 36.03%. In the residual volatilization and coke combustion stage, the weight loss rate begins to slow down, and a large amount of volatile substances are produced while solid coke is also generated. At this time, the mass fraction of the residue is 53.4%.

[0090] Depend on Figure 5It can be seen that sodium ascorbate can be divided into four stages during the heating process. Drying stage (50℃~116.8℃), temperature holding stage (116.8℃~192℃), volatilization and combustion stage (192℃~236℃), residual volatilization and coke combustion stage (236℃~700℃). In the drying stage, it is mainly the moisture in sodium ascorbate, and the weight loss rate reaches the maximum at 93.2℃, with a total weight loss of 0.29%. In the temperature holding stage, the mass of sodium ascorbate absorbed external heat remains basically unchanged. In the volatilization and combustion stage, sodium ascorbate decomposes rapidly at this stage, and the mass drops sharply, with a total mass loss of 44.10%, and the weight loss rate reaches the maximum at 235.6℃.

[0091] Test Example 4

[0092] UV-visible spectrum drawing: Take an appropriate amount of the sample obtained in Example 1 (molar ratio of 2:1) and mix it with deionized water to form a solution, use water as a reference solution, and use a Lambda type UV spectrometer to characterize the sample. The UV spectra of ascorbic acid, sodium ascorbate, and ferrous ascorbate are shown in the figure below: Figure 6 shown.

[0093] Depend on Figure 6 It can be seen that the peak value of 265nm is close to 265.78nm in the literature. The maximum absorption peaks of ferrous ascorbate, sodium ascorbate and ascorbic acid are obviously different. We can infer that ferrous ascorbate is a substance different from sodium ascorbate and ascorbic acid.

[0094] Test Example 5

[0095] Complex ferrous iron content test: Take an appropriate amount of the sample obtained in Example 1 (molar ratio of 2:1) and mix it with deionized water to form a solution, use water as a reference solution, and use a Lambda type ultraviolet spectrometer to measure the absorbance of the sample at a wavelength of 510nm. The specific method is as follows: In a beaker, add 2mL of (1+3) hydrochloric acid in sequence, transfer 2mL of the sample to be tested, add 2mL of 0.5% o-phenanthroline solution, use a pH meter to drop saturated sodium acetate solution to make pH = 5.20, then add 5mL of acetic acid-ammonium acetate buffer solution, 20mL of anhydrous ethanol, and then add water and shake well. Let stand at room temperature for 5 to 10 minutes, use a 1cm colorimetric dish, use water as a reference, and measure the absorbance at a wavelength of 510nm. According to this experimental method, 1, 2, 3, 4, 5, 6, and 7 mg / L of ammonium ferrous sulfate standard concentration colorimetric solution was prepared, and the absorbance of each colorimetric solution was measured. The test results of the absorbance corresponding to the mass concentration of ammonium ferrous sulfate are shown in Table 2, and the standard curve is shown in Figure 7 shown.

[0096] Table 2 Absorbance test data of ferrous ascorbate

[0097]

[0098]

[0099] From Table 2 and Figure 7 It can be seen that the absorbance is linearly related to the mass concentration of ammonium ferrous sulfate. The linear equation obtained by regression is y=0.01116x+0.000363889, and the correlation coefficient R 2 is 0.994. After obtaining the standard curve of the gradient concentration of ammonium ferrous sulfate, the 4 mg / L ferrous ascorbate solution prepared according to the experimental method was divided into three groups to determine the content of complexed iron. Ferrous ascorbate was configured according to the experimental method, and it was found that the proportion of iron in ferrous ascorbate was about 8.45%. In theory, the proportion of ferrous iron in ferrous ascorbate is about 13.7%, which is 5.25% different from the actual situation. It is speculated that it may be related to coordinated water and bound water. In thermogravimetric analysis, the weight of ferrous ascorbate has been decreasing at the beginning, and the weight loss at this time should be coordinated water and bound water. In theoretical calculations, bound water is ignored. Therefore, it can be inferred that there are multiple bound waters in ferrous ascorbate.

[0100] Test Example 6

[0101] DPPH free radical scavenging activity analysis: Accurately pipette 0.4 mL of the sample obtained in Example 1 (molar ratio of 2:1) into a 5 mL centrifuge tube, add 2.0 mL of 0.1 mmol / L DPPH-ethanol solution, and shake well. Let stand in the dark for half an hour, shake continuously, and measure the absorbance at 517 nm using an ultraviolet spectrometer. Each sample to be tested is measured in parallel for 3 groups, record the experimental data, and calculate the scavenging rate P. The calculation formula for DPPH free radical scavenging rate is as follows:

[0102]

[0103] The DPPH free radical scavenging rates of sodium ascorbate, ascorbic acid, niacin, sodium citrate, and ferrous ascorbate are as follows: Figure 8 shown.

[0104] Depend on Figure 8 It can be seen that for all antioxidants, as the concentration increases, the scavenging rate of ferrous ascorbate for DPPH decreases after coordination. The scavenging ability of sodium ascorbate is stronger than that of ferrous ascorbate, while the scavenging ability of ferrous ascorbate is not as good as that of ascorbic acid. However, antioxidants such as nicotinic acid and sodium citrate have weaker scavenging ability for DPPH than sodium ascorbate and ascorbic acid. When the concentration is lower than 30 mg / mL, the scavenging ability of ferrous ascorbate is not as good as that of nicotinic acid and sodium citrate. Therefore, in terms of the scavenging ability for DPPH, the antioxidant performance of ferrous ascorbate is weaker than that of several common antioxidants. At the same time, the weakening of antioxidant performance also means that the stability of ferrous ascorbate has increased.

[0105] Test Example 7

[0106] ABTS + Free radical scavenging activity analysis: 0.5 mL of the sample obtained in Example 1 (molar ratio of 2:1) was added to a 10 mL stoppered cuvette, and then 4 mL of ABTS was added. + Working solution. Use 5mL of anhydrous ethanol as the solution and shake well. Place in a constant temperature water bath at 30°C for 360 seconds and measure the absorbance at 517nm using a UV spectrometer. Perform three parallel tests on each sample to be tested, record the experimental data, and calculate the clearance rate P. Select commonly used water-soluble antioxidants to compare with ferrous ascorbate to determine the antioxidant capacity of ferrous ascorbate. ABTS + The calculation formula of free radical scavenging rate is as follows:

[0107]

[0108] ABTS of sodium ascorbate, ascorbic acid, niacin, sodium citrate, ferrous ascorbate + Free radical scavenging rate Fig. 9 shown.

[0109] Depend on Fig. 9 It can be seen that the antioxidant capacity of ferrous ascorbate is relatively weak as the concentration of all antioxidants increases. When the concentration is lower than 6.25 mg / mL, the scavenging abilities of sodium ascorbate and ferrous ascorbate are similar. When the concentration is 80 mg / mL, the scavenging abilities of ferrous ascorbate and nicotinic acid are similar. Therefore, in terms of the scavenging ability of DPPH, the antioxidant performance of ferrous ascorbate is weaker than that of several common antioxidants. At the same time, the weakening of antioxidant performance also means that the stability of ferrous ascorbate has increased.

[0110] Test Case 8

[0111] Stability test of ferrous ascorbate: The decomposition of ferrous ascorbate obtained in Example 1 (molar ratio of 2:1) in deionized water, tap water (Laboratory 603, Block A, Stanley Ho Building, Zhongkai University of Agriculture and Engineering), deionized water with different hydrogen ion concentration indexes, and tap water was studied using UV-visible spectrophotometry to meet the needs of actual production. The pH value was adjusted with acetic acid and sodium bicarbonate, and the pH value was measured with a pH meter. 500 mL of tap water and deionized water with pH = 2, 4, 6, 7, and 8 were prepared. Then, 0.001 g / L of ferrous ascorbate solution was prepared with tap water or deionized water of each pH value, and a small amount of solvent was absorbed into a cuvette. Then, the highest absorption peak was measured with a Lambda type ultraviolet spectrometer, and then the absorbance curve with time was measured with an ultraviolet spectrophotometer. The absorbance curve with time at different pH values ​​is shown in FIG. Figures 10 to 14 shown.

[0112] Depend on Fig.10 It can be seen that under the condition of pH=2, the maximum absorption wavelength of ferrous ascorbate shifts and decreases to around 245nm, which means that under the condition of pH=2, the maximum time that ferrous ascorbate can exist stably is 50min.

[0113] Depend on Fig.11 It can be seen that under the condition of pH = 4, the maximum absorption wavelength of ferrous ascorbate also shifts to around 245nm. This indicates that under the condition of pH = 4, the maximum time that ferrous ascorbate can exist stably is 100 minutes.

[0114] Depend on Fig.12 It can be seen that under pH = 6, the maximum absorption wavelength of ferrous ascorbate is near 265nm. This means that under pH = 6, the maximum time that ferrous ascorbate can exist stably is 100 minutes.

[0115] Depend on Fig.13 It can be seen that under pH=7, the maximum absorption wavelength of ferrous ascorbate is located near 265nm, which indicates that zinc ascorbate can exist stably under pH=7.

[0116] Depend on Fig.14 It can be seen that under the condition of pH=8, the maximum absorption wavelength of ferrous ascorbate is located near 265nm. This means that under the condition of pH=8, the maximum time that ferrous ascorbate can exist stably is 50min.

[0117] In summary, ascorbic acid will become less stable and easily decompose and inactivate when the pH value is too low or too high; ferrous ascorbate also has a similar situation. Therefore, it can be inferred that the aqueous solution of ferrous ascorbate is more stable when the pH is between 6 and 7.

[0118] Test Example 9

[0119] Study on antibacterial activity: The agar diffusion method was used to determine the antibacterial ability of ferrous ascorbate obtained in Example 1 (molar ratio of 2:1) against Escherichia coli and Staphylococcus aureus. After sterilization, the required sample was placed on a clean workbench, and 20 mL of sterilized agar medium was poured into the culture dish at 60°C, waiting for cooling and solidification. Then 100 μL of the live bacterial suspension was aspirated and used a spreader to evenly inoculate it on the surface of the agar plate. Use a hole puncher to punch a circular hole of exactly the same diameter on the agar medium, and add 80 μL of sample to each hole. Encapsulate the culture dish and place it in a 37°C incubator for 24 hours. Take out the culture dish every 24 hours, use a vernier caliper to measure the diameter of the inhibition zone several times, take pictures and record them. The test results of the agar diffusion method are as follows: Figures 15-16 shown.

[0120] Depend on Figures 15-16 It can be seen that the size of the inhibition zone of ascorbic acid and ferrous ascorbate decreases with time. In the test of inhibiting the activity of Staphylococcus aureus, from the change of the inhibition zone (compared with the inhibition zone at 24h), the inhibition zone of ascorbic acid decreased by 23% cumulatively, and the inhibition zone of ferrous ascorbate decreased by 4% cumulatively; it can be inferred that ascorbic acid and ferrous ascorbate have good inhibitory effects on Staphylococcus aureus and the antibacterial effect of ferrous ascorbate is better than ascorbic acid. In the experiment of inhibiting the activity of Escherichia coli, compared with the change of the inhibition zone at 24h, the inhibition zone of ascorbic acid decreased by 100% cumulatively, and the inhibition zone of ferrous ascorbate decreased by 17% cumulatively; it can be inferred that the antibacterial effect and antibacterial time of ferrous ascorbate are better than ascorbic acid. Escherichia coli is in a sublethal state at pH = 3.0 ~ 4.6, and has a strong acid resistance; at pH = 4.7 ~ 7.0, the growth of Escherichia coli is good. Ferrous ascorbate will produce a Fenton-like reaction, generating hydroxyl free radicals, which can combine with hydrogen ions on the bacterial cell membrane to cause them to lose their normal physiological functions, thereby achieving an antibacterial effect.

[0121] Test Example 10

[0122] Bacterial growth curve determination: The OD values ​​of Escherichia coli and Staphylococcus aureus treated with ascorbic acid and ferrous ascorbate obtained in Example 1 (molar ratio of 2:1) for 96 h were determined using an ELISA instrument. 630 After sufficient irradiation with ultraviolet sterilization lamp, add 400μL of bacterial solution and 1600μL of sterilized LB broth liquid culture medium into a sterile test tube in a sterile clean bench. After slight shaking, add 2000μL of drug sample and place it in a 37℃ shaker for 96h. During the culture period, pipette 200μL of bacterial solution into a sterile 96-well plate at regular intervals and use an enzyme reader to measure the OD of the bacterial solution. 630 Value, each sample was processed in parallel for 3 experiments. Then 100 μL of the bacterial solution after 96 hours of incubation was evenly inoculated on the surface of the agar solid culture medium. It was placed in a 37°C incubator for 24 hours, and the colony formation on the agar was recorded and photographed. Each sample was processed in parallel for 3 experiments. OD of Escherichia coli and Staphylococcus aureus cultured with ascorbic acid and ferrous ascorbate 630 The growth curve of Figures 17-18 shown.

[0123] Depend on Figures 17-18 It can be seen that the bacterial solution treated with ascorbic acid and ferrous ascorbate had a significant antibacterial effect at 24 hours. In the Staphylococcus aureus group, the OD of the bacterial solution treated with ascorbic acid was significantly increased due to the increase in the metabolites of Staphylococcus aureus. 630 The value of OD increased to a certain extent; however, the OD of the bacterial solution treated with ferrous ascorbate was 630The value of remained basically unchanged. In the E. coli group, there was a similar situation. The OD of the bacterial solution treated with ascorbic acid 630 The value of OD increased significantly, and the OD of the bacterial solution treated with ferrous ascorbate 630 The value remains basically unchanged.

[0124] Test Example 11

[0125] Determination of minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC): The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of ferrous ascorbate against Staphylococcus aureus and Escherichia coli were determined by standard microdilution method. 20 μL of bacterial suspension and 80 μL of sterilized LB broth were added to the wells of a 96-well plate on a clean bench. After slight shaking, 100 μL of ferrous ascorbate solution diluted with different concentrations of Example 1 (molar ratio of 2:1) was added respectively. The 96-well plate was covered and sealed, and placed in a 37°C shaker for incubation for 24 hours. During the culture period, the OD of the bacterial solution was measured using an ELISA reader at regular intervals. 630 100 μL of the bacterial solution after 24 hours of incubation was evenly spread on the surface of agar solid culture medium, incubated in a 37°C incubator for 24 hours, and the colony formation on agar was photographed and recorded. Three parallel experiments were performed for each treatment. The OD values ​​of Staphylococcus aureus and Escherichia coli after treatment with ferrous ascorbate at different concentrations were calculated. 630 Growth curve to determine its MIC and MBC, growth curve such as Figures 19-20 shown.

[0126] Depend on Figures 19-20 It can be seen that the OD of the co-culture of the ferrous ascorbate solution with a higher concentration and the bacterial solution of Staphylococcus aureus and Escherichia coli is 630 The values ​​were compared to a straight line and decreased over time; the OD of the low concentration of ferrous ascorbate solution co-cultured with Staphylococcus aureus and Escherichia coli was 630 The value will show a slow growth trend as time goes by. When the treatment concentration is 0.125mg / mL, the activity of Staphylococcus aureus is greatly inhibited compared with the control group, slowing down the reproduction and development of bacteria; when the treatment concentration is 0.0625mg / mL, the activity of Escherichia coli is greatly inhibited compared with the control group, slowing down the reproduction and development of bacteria. When the treatment concentration is >0.125mg / mL, the OD value of Staphylococcus aureus is 0.0625mg / mL. 630 The value does not increase or even shows a negative growth trend, indicating that the activity of the bacteria is completely inhibited and cannot grow and reproduce normally or the bacteria are killed and completely lose their activity; when the treatment concentration is >0.125mg / mL, the OD of the Escherichia coli solution 630If the value does not increase or even shows a negative growth trend, it means that the activity of the bacteria is completely inhibited and it is unable to grow, develop and reproduce normally, or the bacteria are killed and completely lose their activity.

[0127] Test Example 12

[0128] DNA interaction test: Use a UV-visible spectrophotometer to test the interaction between the ferrous ascorbate obtained in Example 1 (molar ratio of 2:1) and DNA. Add 1 mL of 0.16 mmol / L ferrous ascorbate solution to 5 10 mL stoppered colorimetric tubes, and then add 0 mL, 1 mL, 2 mL, 3 mL, and 4 mL of 0.02 mmol / L DNA solution, respectively. Dilute to the scale with Tris-HCL buffer, react at 25 ° C for half an hour, and scan in the wavelength range of 200-350 nm. The test results of the interaction between ferrous ascorbate and different concentrations of DNA are shown below. Fig.21 shown.

[0129] Depend on Fig.21 It can be seen that as the amount of DNA solution increases, the ultraviolet absorption spectrum changes. For ferrous ascorbate, as the amount of DNA solution increases, its characteristic peak continues to blue shift; it can be inferred that ferrous ascorbate reacts with DNA. After adding the DNA solution, a strong absorption peak appears near 209nm, which is the ultraviolet absorption peak of DNA. And as the amount of DNA solution increases, the ultraviolet absorption spectrum changes. The phenomenon of metal complex binding to DNA is the red shift of the characteristic peak of DNA's ultraviolet absorption.

[0130] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A method for preparing ferrous ascorbate, characterized in that: The following steps are involved: Mixing sodium ascorbate, ferrous sulfate and water to perform double decomposition reaction to obtain a reaction solution; The reaction solution is mixed with ethanol to precipitate the ferrous ascorbate.

2. The preparation method according to claim 1, characterized in that: The ferrous sulfate is hydrated ferrous sulfate; The molar ratio of the sodium ascorbate to ferrous sulfate is 2-3:

1.

3. The preparation method according to claim 1, characterized in that: The volume ratio of the amount of sodium ascorbate to water is 1 mol: 1 to 50 mL.

4. The preparation method according to claim 1, characterized in that: The temperature of the double decomposition reaction is 30-70° C., and the time is 30-180 min.

5. The preparation method according to claim 1 or 4, characterized in that: The double decomposition reaction is carried out under stirring conditions; the stirring speed is 200-400 rpm.

6. The preparation method according to claim 1, characterized in that: The ethanol is anhydrous ethanol; the mass ratio of water to ethanol is 5-15:10-30.

7. The preparation method according to claim 6, characterized in that: After the reaction solution and ethanol are mixed, the precipitated solid is freeze-dried; the freeze-drying temperature is -80 to -20°C and the time is 18 to 72 hours.

8. Ferrous ascorbate obtained by the preparation method according to any one of claims 1 to 7, characterized in that: The iron content of the ferrous ascorbate is 8% to 13%.

9. Application of ferrous ascorbate in the preparation of antibacterial preparations.

10. Application of ferrous ascorbate in DNA detection.

Citation Information

Patent Citations

  • Hydrogen sulfate ferrous ascorbate and preparation method and application thereof

    CN106699816A